De combatientes a vecinos: hacer una vida después de los acuerdos de paz en Colombia. Un relato etnográfico sobre San José de León (2022)
The research that gave rise to this article explored, from a qualitative perspective, with a narrative and ethnographic focus, the daily process through which people in disarmament, demobilization and reintegration (DDR) processes in Colombia experience, after the 2016 peace agreement, having as methodological strategies the approaches of narrative practices and their expression in textile narratives. The article collects the experience of a group of peace signatories in San José de León, Mutatá, Antioquia, in order to understand, from their own voices and practices, the paths traveled towards building and managing their new living environment, through a sensitive approach to this group of new neighbors, to influence the narratives of the “enemy” sustained during decades of conflict. From the analysis of the implementation of the peace agreement, a description is presented of the arrival of former combatants to the territory, identifying dynamics, practices and daily transformations that have made it possible to build this new home. Based on the empirical data, the paradoxes, complexities and challenges are presented, but also the possibilities for building and/or reconstructing social relations in the local context, between the peace signatories, their families and their new neighbors, as a complex process dynamic.